Зрілість системи кібербезпеки країни в умовах війни: тенденції оцінювання - Доценко Т. В.; Кузьменко М. В (НТУ "ДП", 2024)
Результати. Визначено останні тенденції оцінювання зрілості системи кібербезпеки країни, враховуючи аспект військових умов: проаналізовано існуючу нормативно-правову законодавчу базу міжнародного та національного рівнів; сформульовано поняття зрілості та оцінювання зрілості системи кібербезпеки країни під час військових дій. У роботі окреслено ключові елементи оцінки зрілості національної системи кібербезпеки в умовах проведення воєнних операцій: адаптивність, суміжність, готовність, партнерство, кіберрезерви, вразливості та загрози, навчання. Визначено основні вектори оцінювання: оцінка кіберзагроз, кібератак, захисту інфраструктури, взаємодії суб’єктів кібербезпеки, рівня підготовки кадрів; виокремлено новітні підходи оцінки системи. Сформовано схему майбутніх ключових викликів, тенденцій, рекомендацій щодо оцінки зрілості національної системи кібербезпеки в умовах війни. Results. The latest trends in assessing the maturity of the country's cybersecurity system, taking into account the aspect of military conditions, are identified: the existing regulatory and legal framework at the international and national levels is indicated; the concept of maturity and assessment of the maturity of the country's cybersecurity system during military operations is formulated. The paper outlines the key elements of assessing the maturity of the national cybersecurity system in military operations: adaptability, interoperability, readiness, partnership, cyber reserves, vulnerabilities and threats, and training. The main vectors of assessment are identified: assessment of cyber threats, cyber attacks, infrastructure protection, interaction of cybersecurity actors, level of personnel training; the latest approaches to system assessment are noted. A scheme of future key challenges, trends, and recommendations for assessing the maturity of the national cybersecurity system in wartime has been formed.
Maturity of the country's cybersecurity system in the conditions of war: assessment trends
Keywords: кібербезпека; зрілість системи; методики оцінювання; моделювання берзахисту; кіберризики; кібервразливості; cybersecurity; system maturity; assessment methods; cyber defence modelling; cyber risks; cyber vulnerabilitie cybersecurity; cyber vulnerabilities